Linear system of differential equations with turning point - Klyuchnyk, I. H. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
A system of linear differential equations with small parameter as a coefficient of a part of derivatives is reduced to the canonical form and the properties of the transformation matrix are investigated.